Gotham. The fifth and final season [videorecording (DVD)] - Cannon, Danny; Cannon, Danny; Shaw Milito, Louis; McKenzie, Ben, 1979-; Logue, Donal, 1966-; Mazouz, David, 2001- (Warner Bros. Entertainment, 2019)
Follows James Gordon during his early days of the Gotham City Police Department.